Modelling the Kinetics Molybdenum Reduction Rate by Morganella sp. (Journal of Environmental Microbiology and Toxicology, 2020)
Simulation of physical, chemical or biological data by mathematical approach can aid the researcher explain the physicochemical or biochemical phenomenon. Mathematical models can also be utilized to estimate or predict the possible actions, to replicate a prediction or retroactivity and to schedule better experiments. Bacteria are an emerging instrument for the bioremediation of the molybdenum pollutant in the world, molybdenum reduction into insoluble molybdenum blue. In this study, the molybdenum reduction rate by the bacterium Morganella sp. was studied for its inhibitory kinetics characteristics using sodium molybdate as a substrate. Modeling kinetics showed that molybdenum reduction could be explained by several models such as Monod, Haldane, Hans-Levenspiel, Luong, Teissier, Aiba and Yano with Aiba as the best model as judged using error function analysis such as bias and accuracy factors (BF and AF), root mean square error (RMSE), adjusted coefficient of determination (adjR2), and corrected Akaike Information Criterion (AICc). The calculated value for the Teissier-Edward’s constants, which are qmax, Ks, and Ki that are maximal reduction rate, half saturation constant for maximal reduction, half saturation constant for inhibition of reduction were 7.77 (95% C.I., 4.41 to 19.95) µmol Mo-blue hr-1, 26.63 (95% C.I., 12.82 to 40.44) mM and 51.39 (95% C.I., 23.67 to 79.10) mM, respectively. The true maximal reduction rate, which occurred when the slope of the curve is zero occurs at 36 mM molybdate concentration and a corresponding value of 1.85 µmol Mo-blue hr-1. The model parameters obtained revealed that Morganella sp. have strong resistance to higher toxic molybdenum levels indicating the usefulness of this bacterium for bioremediation.
Keywords: Bacterium; Molybdenum blue; Toxicity; Modelling; Bioremediation